DEVELOPMENT OF LEADERSHIP QUALITIES THROUGH METHODS OF DIRECT EXPERIENCE OF LIVE LIVING - Balte-Balciuniene, Rasa; Kharitonova, Tatiana (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of this study was to examine the problem of the formation of a special mindset of the leader. The training of leaders (AUTHENTICS program, HAI.LT institute) is focused on the shaping of independent decision-making and freedom from stereotypes. In order to break out from automatic reactions of the brain and create novelty, we taught leaders to reflect on his/her emotional reactions that arise in situations of real-life – live living. AUTHENTIC program of consciousness leadership is a modular training program held by HAI.LT Institute since 2011. We conducted a psychological study of participants of the leadership training program (44 leaders, 2013 - 2015). Results of the study showed the changes in value orientations, in the behavioural priorities in the locus of control, also in the stereotypical beliefs, and motivation of decisions.